Tumor de células de granulosa en un bovino gestante : reporte de un caso (2000)
ABSTRACT: Ovarian neoplasms are not common in bovine; it must be taken in account for differential diag-nosis in endocrine diseases. These neoplasms are functional; it means that it produces hormones and in addition to the proliferative problem of the tumour, they cause a great variety of clinical features. In this report, we describe a very exceptional case in a bovine female with a granullosa cell tumour and an advanced normal pregnancy at the same time.